1991
DOI: 10.1152/ajpregu.1991.261.6.r1497
|View full text |Cite
|
Sign up to set email alerts
|

Role of angiotensin in ameliorating the renal actions of norepinephrine

Abstract: To determine the importance of the arterial pressure effects of angiotensin II (ANG II) on renal function during acute renal adrenergic stimulation, we examined the effects of a 2-h intrarenal arterial infusion of norepinephrine (NE) at 0.1 and 0.25 micrograms.kg-1.min-1 on renal function in five conscious dogs during 1) control conditions, 2) servo-control of renal arterial pressure (RAP) at control levels, and 3) chronic captopril administration. The low rate of NE infusion produced an approximately 20% decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…A more or less pronounced decrease in renal function following ACEI administration has been described in dogs with experimental renal artery stenosis (Brooks et al. , 1992), acute renal adrenergic stimulation (Yang & Lohmeier, 1991), or excessive ACEI dosages (MacDonald et al. , 1987).…”
Section: Acute Renal Failurementioning
confidence: 99%
“…A more or less pronounced decrease in renal function following ACEI administration has been described in dogs with experimental renal artery stenosis (Brooks et al. , 1992), acute renal adrenergic stimulation (Yang & Lohmeier, 1991), or excessive ACEI dosages (MacDonald et al. , 1987).…”
Section: Acute Renal Failurementioning
confidence: 99%
“…3 " 13 In previous studies, acute blockade of the renin-angiotensin system either has attenuated or has had no effect on the RBF response to adrenergic stimulation. In contrast, in two earlier studies from our laboratory we observed that long-term administration of captopril actually increased the sensitivity of the renal vasculature to chronic intrarenal infusions of NE, causing severe renal ischemia at rates of NE infusion that produced only moderate reductions in renal plasma flow in dogs with a functional renin-angiotensin system.…”
Section: Discussionmentioning
confidence: 96%
“…In previous studies, we observed that captopril enhanced the renovascular response to intrarenal infusions of NE that produced 20-40% reductions in renal plasma flow when the renin-angiotensin system was intact. 6 - 13 However, since renal plasma flow was determined only after hours to days of continuous renal adrenergic stimulation, the significance of these findings is unclear because it is uncertain that neurally induced reductions in RBF of this magnitude would be sustained for such long periods of time under either physiological or pathophysiological conditions. The present results, on the other hand, showed that severe renal ischemia may occur very abruptly during moderate increments in renal adrenergic stimulation when the renin-angiotensin system is chronically blocked with captopril.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tubular lesions, interstitial fibrosis, and interstitial inflammatory cell infiltrate were scored similarly from 0 (normal) to 3 (severe change)(from [50]). dogs [66,67]. Acute renal failure potentially due to ACE inhibitors has been reported in dogs treated with captopril [68], enalapril [68] and benazepril [69].…”
Section: Specific Adverse Effects Of Ace Inhibitors Reported In Dogsmentioning
confidence: 99%